Concordance of cerebrospinal fluid real‐time quaking‐induced conversion across the European Creutzfeldt–Jakob Disease Surveillance Network. (25th May 2022) - McKenzie, Neil; Piconi, Gabriele; Culeux, Audrey; Hammarin, Anna‐Lena; Stergiou, Christos; Tzartos, Socrates; Versleijen, Alexandra A. M.; van de Geer, Jacqueline; Cras, Patrick; Cardone, Franco; Ladogana, Anna; Mannana, Angela; et al.
Abstract: Background and purpose: Cerebrospinal fluid (CSF) real‐time quaking‐induced conversion (RT‐QuIC) has a high degree of sensitivity and specificity for the diagnosis of sporadic Creutzfeldt–Jakob disease (sCJD) and this has led to its being included in revised European CJD Surveillance Network diagnostic criteria for sCJD. As CSF RT‐QuIC becomes more widely established, it is crucial that the analytical performance of individual laboratories is consistent. The aim of this ring‐trial was to ascertain the degree of concordance between European countries undertaking CSF RT‐QuIC. Methods: Ten identical CSF samples, seven from probable or neuropathologically confirmed sCJD and three from non‐CJD cases, were sent to 13 laboratories from 11 countries for RT‐QuIC analysis. A range of instrumentation and different recombinant prion protein substrates were used. Each laboratory analysed the CSF samples blinded to the diagnosis and reported the results as positive or negative. Results: All 13 laboratories correctly identified five of the seven sCJD cases and the remaining two sCJD cases were identified by 92% of laboratories. Of the two sCJD cases that were not identified by all laboratories, one had a disease duration >26 months with a negative 14‐3‐3, whilst the remaining case had a 4‐month disease duration and a positive 14‐3‐3. A single false positive CSF RT‐QuIC result was observed in this study. Conclusions: This study shows that CSF RT‐QuIC demonstrates an excellent concordance between centres, even when using a variety of instrumentation, recombinant prion protein substrates and CSF volumes. The adoption of CSF RT‐QuIC by all CJD surveillance centres is recommended.